Revision of the New Zealand species of the Genus Pselaphogenius Reitter (Staphylinidae: Pselaphinae: Pselaphitae: Pselaphini) - Owens, Brittany E.; Carlton, Christopher E. (Zootaxa, 2022)
Species within the genus Pselaphogenius Reitter occurring in New Zealand are revised. Twenty-three species are known from the region and can be divided into two distinct species groups. Fifteen new species are described: Pselaphogenius calantica Owens and Carlton, sp. nov.; Pselaphogenius chandleri Owens and Carlton, sp. nov.; Pselaphogenius cornus Owens and Carlton, sp. nov.; Pselaphogenius dismukesi Owens and Carlton, sp. nov.; Pselaphogenius elephantus Owens and Carlton, sp. nov.; Pselaphogenius fimbria Owens and Carlton, sp. nov.; Pselaphogenius gibbus Owens and Carlton, sp. nov.; Pselaphogenius jiaweii Owens and Carlton, sp. nov.; Pselaphogenius kalleri Owens and Carlton, sp. nov.; Pselaphogenius kangi Owens and Carlton, sp. nov.; Pselaphogenius lescheni Owens and Carlton, sp. nov.; Pselaphogenius moerewae Owens and Carlton, sp. nov.; Pselaphogenius otteai Owens and Carlton, sp. nov.; Pselaphogenius parki Owens and Carlton, sp. nov.; Pselaphogenius stouti Owens and Carlton, sp. nov.. Pselaphogenius citimus (Broun), 1893, Pselaphogenius delicatus (Broun), 1886, and Pselaphogenius ventralis (Broun), 1895 were transferred from the genus Pselaphus Herbst (Jeannel 1951) and are herein redescribed. Additionally, the species Pselaphus caecus Broun, 1886 is transferred to the genus Pselaphogenius comb. nov.. Habitus photographs, distributional maps, and line drawings of diagnostic characters for each species are provided. A regional checklist and key to are provided to species of the genus occurring in New Zealand.